Respuesta :

2(6−2x)−2x=2(5+x)−4

Use the distributive property to multiply 2 by 6−2x.

12−4x−2x=2(5+x)−4

Combine −4x and −2x to get −6x.

12−6x=2(5+x)−4

Use the distributive property to multiply 2 by 5+x.

12−6x=10+2x−4

Subtract 4 from 10 to get 6.

12−6x=6+2x

Subtract 2x from both sides.

12−6x−2x=6

Combine −6x and −2x to get −8x.

12−8x=6

Subtract 12 from both sides.

−8x=6−12

Subtract 12 from 6 to get −6.

−8x=−6

Divide both sides by −8.

x = -6/-8  

Reduce the fraction -6/-8   to lowest terms by extracting and canceling out −2.

x= 3/4